Article Commentary: The Who, the What, and the How: A Description of Strategies and Lessons Learned to Expand Access to Medications for Opioid Use Disorder in Rural America. Issue 2 (April 2021) - Cole, Evan S.; DiDomenico, Ellen; Green, Sherri; Heil, Susan K. R.; Hilliard, Tandrea; Mossburg, Sarah E.; Sussman, Andrew L.; Warwick, Jack; Westfall, John M.; Zittleman, Linda; Salvador, Julie G.
Access to treatment for opioid use disorder (OUD) in rural areas within the United States remains a challenge. Providers must complete 8–24 h of training to obtain the Drug Addiction Treatment Act (DATA) 2000 waiver to have the legal authority to prescribe buprenorphine for OUD. Over the last 4 years, we executed five dissemination and implementation grants funded by the Agency for Healthcare Research and Quality to study and address barriers to providing Medications for Opioid Use Disorder Treatment (MOUD), including psychosocial supports, in rural primary care practices in different states. We found that obtaining the DATA 2000 waiver is just one component of meaningful treatment using MOUD, and that the waiver provides a one-time benchmark that often does not address other significant barriers that providers face daily. In this commentary, we summarize our initiatives and the common lessons learned across our grants and offer recommendations on how primary care providers can be better supported to expand access to MOUD in rural America.